The Reflection on the Originality of the Study of Physical Education, Health and Sport Sciences in Japan - Koji Takahashi (The Asian Journal of Kinesiology, 2024)
OBJECTIVES The purpose of this study is to discuss the redefinition of the Physical Education, Health, and Sport Sciences (PEHSS) in Japan by considering its originality. METHODS The method of this study is reflective consideration in philosophy. The steps of this consideration are understanding of the study of PEHSS, analysis of its current status, extensions and inclusions of the study kinesiology/biomechanics and sport movement & behaviour that related to the PEHSS, and my opinion and proposals regarding the study of PEHSS. RESULTS First, the “Japan Society of Physical Education, Health and Sport Sciences (JSPEHSS)” is commonly known as the “TAIIKU-GAKKAI” in Japanese. The JSPEHSS is cooperation with science and research bodies of The Science Council of Japan and belongs to the Branches of Health and Sport Sciences in the Life Sciences Section. In addition, PEHSS is included in the Health Science, especially, rehabilitation, sports, physical education, nutrition, and health science-related at the Grants-in-Aid for Scientific Research of Japan Society for the Promotion of Science. Second, the name and the purpose of the JSPEHSS have undergone several revisions. These revisions have been influenced by the shift from “Physical Education” to “Sports” in Japanese society and culture. Third, kinesiology in Japan has established two standpoints which are biomechanics and theory of sport movement & behaviour. Coaching is included in the latter standpoint. CONCLUSIONS I propose that the alternative name for the study of PEHSS be changed to “the system of knowledge related to human body and movement practice.” The reasons for my opinion are that PEHSS is a field based on human “practice,” the object of research is the human body and movement practice/ physical activity in general, and the research method is integrated/synthetic science, including Natural Sciences, Humanities and Social Sciences.